A comparative study of single versus repeat instillation of intravaginal prostaglandin E2 gel for induction of labour - Mashkaria, Aastha; Shah, Sushma R.; Mehta, Ami V.; Panchal, Payal P.; Mashkaria, Aashka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The aim of induction was to achieve successful vaginal delivery where continuation of pregnancy is not desirable. Unfavourable cervix is one of the main causes of failed induction. Introduction of intravaginal prostaglandins E2 has revolutionised the method of cervical ripening. More than one dose of prostaglandin E2 (PGE2) gel may be necessary to facilitate cervical ripening and increase the chances of vaginal delivery. Methods: This retrospective study was done to find the efficacy of repeat instillation of intravaginal PGE2 gel and to compare the maternal and fetal outcome between the single instillation group and repeat instillation group. The women who went into labour or achieved cervical ripening with a single instillation of PGE2 gel forms Group A. Those who required repeat instillation of PGE2 gel forms Group B. Both groups were compared for specific parameters. Results: Primigravidas required repeat instillation. Postdated pregnancy was the most common indication for induction of labour. 45.2% of primis required only single dose and 54.8% required repeat dose. About two third (77.8%) of multipara required only one dose and a third of multipara needed repeat dose. In Group A 90.7% had vaginal delivery, 9.3% had Caesarean section. Group B 95.7% had vaginal delivery and 4.3% had Caesarean section. Conclusions: Prostaglandins PGE2 (0.5 mg) gel is recommended to be used intravaginally. We applied 2 doses of intravaginal PGE2, 24 hours apart and no complications like uterine hyperstimulation was seen. There is no increased fetal risk with repeat instillation of intravaginal PGE2 gel.